The Droplet Measurement Application Software of Jet Pulse System Portable Fogging Machine Using Image Processing - Junaid Sadrach; Prayoga Bakti; Sri Kadarwati (LIPI Press, Anggota IKAPI, 2013)
Jet pulse system portable fogging machine is used to control pest, vector, damaging micro organism and unpleasant odor. The machine produces and sprays out fog. One of the fogging machine testing parameters is droplet size accuracy level testing complying with SNI-05-7190-2006. At the moment, the droplet measurement is done by manual estimation using scaled microscope, but this method is not effective. Therefore, a new method is needed to support the testing effectively and efficiently. As a result, application software to measure droplet diameter of the fogging machine is made. The droplet diameter measurement result has been tested and it is certain that the result is close to the values of manual estimation. Therefore, the software can also be used to support the conduction of fogging machine testing. Keywords: fogging machine, SNI-05-7190-2006, droplet, testing